Effect of a Small Physiological Electric Field on Angiogenic Activity in First-Trimester Extravillous Trophoblast Cells. (June 2019) - Ye, Liyan; Guan, Linbo; Fan, Ping; Liu, Yinghui; Xiong, Wei; Liu, Rui; Wei, Xing; Zhu, Yue; Liu, Yu; Bai, Huai
Electrical stimulation induces significant angiogenesis in vivo. We have shown that electrical stimulation of trophoblast cells has important functions in aspects of angiogenesis. In this study, we investigated the effects of a direct current electrical field on trophoblast angiogenic tube formation. A 6-hour exposure to electric fields ranging from 50 to 150 mV/mm dose dependently increased tube growth and network formation. Additionally, the effect was time dependent, with increased tube formation occurring between 4 and 8 hours, indicating stimulation of trophoblast cell angiogenesis. Electrical fields of small physiological magnitude stimulated vascular endothelial growth factor expression by trophoblast cells in the culture. Electric field treatment also resulted in activation of Akt, while the activity of extracellular-regulated kinase 1/2, p38, and c-Jun NH2-terminal kinase was not significantly changed. Pretreatment with the vascular endothelial growth factor receptor (VEGFR)-2 inhibitor, SU1498, resulted in potent inhibition of tube growth, and the Akt inhibitor, MK-2206 2HCl, significantly reduced electric field-stimulated tubulogenesis. These data suggest the importance of the VEGFR-2 signaling pathway during electric field-induced trophoblastic angiogenesis. This novel evidence indicates that endogenous electrical fields may promote angiogenesis of trophoblast cells by stimulating the VEGFR signaling pathway.